2019
DOI: 10.1111/1346-8138.14798
|View full text |Cite
|
Sign up to set email alerts
|

Sudden elevation of plasma D‐dimer levels induced by the combination therapy of dabrafenib and trametinib: Report of two cases

Abstract: The combination therapy of dabrafenib and trametinib revolutionized the treatment for BRAF V600‐mutated melanoma. Various adverse events have been reported for this treatment, most notably fever. Herein, we report two cases of novel an adverse event, namely sudden and significant elevation of plasma D‐dimer level induced by this therapy. In the first case, the remarkable elevation of plasma D‐dimer level up to 87.4 mg/dL was noted on day 11, and in the second case, the plasma D‐dimer level reached 125.5 mg/dL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 12 publications
(26 reference statements)
0
12
0
Order By: Relevance
“…CombiDT has been reported in only two patients; 6 moreover, that induced by CombiEB has never been reported. Furthermore, concomitant use of edoxaban with CombiEB prevented not only elevation of D-dimer but also other AEs including pyrexia, gastrointestinal symptom, and malaise.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…CombiDT has been reported in only two patients; 6 moreover, that induced by CombiEB has never been reported. Furthermore, concomitant use of edoxaban with CombiEB prevented not only elevation of D-dimer but also other AEs including pyrexia, gastrointestinal symptom, and malaise.…”
Section: Discussionmentioning
confidence: 95%
“…Although Akino et al 6 advocate two possibilities of increased D-dimer by BRAF/MEK inhibitors, DIC and thrombotic microangiopathies (TMA), its exact cause remains to be elucidated. In our case, although decreased platelet count, anemia, and renal dysfunction were observed at the occurrence of coagulation abnormality, it is difficult to conclude that it was accounted for by TMA.…”
Section: Discussionmentioning
confidence: 99%
“…Such cases are uncommon, and only two similar cases have been reported although a few cases of DIC with vemurafenib monotherapy have been reported. 2,3 These previous two cases also showed pyrexia and increased CRP. 2 Additionally, our case involved a remarkable increase of procalcitonin, and such cases are also rare.…”
mentioning
confidence: 76%
“…2,3 These previous two cases also showed pyrexia and increased CRP. 2 Additionally, our case involved a remarkable increase of procalcitonin, and such cases are also rare. The pyrexia may arise from increased inflammatory cytokines including IL-6 due to combi-DT-induced paradoxical mitogen-activated protein kinase (MAPK) activation.…”
mentioning
confidence: 76%
“…Until now the exact cause of pyrexia development is still unclear but the release of proinflammatory proteins and cytokines seem to play a central role as it has been noted before (Menzies et al, 2015;Clay et al, 2018;Hajek et al, 2018;Maeda et al, 2019;Akino et al, 2019, Kim et al 2019. In patients under therapy with BRAF/MEK inhibitors but also by in-vitro experiments it could be demonstrated that the BRAF inhibitor dabrafenib induces IL-1beta (IL-1β) to a greater extent than the other BRAF inhibitors which are associated less frequently with pyrexia.…”
Section: Discussionmentioning
confidence: 97%